Extracellular Vesicles Derived From Streptococcus anginosus Aggravate Lupus Nephritis by Triggering TLR2‐MyD88‐NF‐κB Signalling in NK Cells - Ying Gong; Lingyue Jin; Lina Duan; Jie Xiao; Yao Li; HongXia Wang; Haifang Wang; Wanying Lin; Yi Zhang; Xiufeng Gan; Shuyin Pang; Yurong Qiu; et al. (Journal of Extracellular Vesicles)
ABSTRACT Systemic lupus erythematosus (SLE) has been linked to gut microbiome dysbiosis, notably an overabundance of Streptococcus anginosus; however, the impact of this microbial imbalance on disease pathogenesis remains unclear. Here, we investigated the contribution of S. anginosus‐derived extracellular vesicles (SA‐EVs) to SLE progression, with an emphasis on lupus nephritis (LN). Fifty‐four SLE patients and 43 healthy controls (HC) were recruited. The faecal, blood and serum samples from participants were collected. SLE disease activity (SLEDA) was evaluated by the SLEDA Index (SLEDAI). Stool S. anginosus abundance was quantified by quantitative PCR, NK cell activation by flow cytometry and serum proinflammatory cytokines profile by ELISA. Lupus‐prone MRL/lpr mice were orally administered SA‐EVs to evaluate in vivo inflammatory responses, renal NK cell activation and renal histopathological changes. S. anginosus levels were significantly elevated in SLE patients relative to HC, positively correlated with SLEDAI scores and NK cell cytotoxicity. In vitro, SA‐EVs stimulation of patient NK cells significantly heightened proinflammatory mediator production (granzyme B, TNF‐α), increased cytotoxicity and downregulated inhibitory receptors (TIM‐3, NKG2A, TIGIT) compared to control EVs from S. Salivarius (SS‐EVs). Mechanistically, lipoteichoic acid (LTA) within SA‐EVs engaged Toll‐like receptor 2 (TLR2) on NK cells, activating MyD88/NF‐κB signalling pathway. In MRL/lpr mice, SA‐EVs treatment increased renal immune complex deposition, upregulated renal NK cell activation markers (NKp44, NKp46), and exacerbated LN pathology with greater immune cell infiltration and inflammatory cytokine levels. Furthermore, NK cell depletion with anti‐NK1.1 antibodies significantly prolonged survival in SA‐EVs administered mice. Thus, SA‐EVs exacerbate SLE by hyperactivating NK cells via the TLR2‐MyD88‐NF‐κB pathway, leading to amplified systemic inflammation and aggravated LN. These findings underscore the potential of targeting SA‐EVs for therapeutic intervention in SLE.